If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -4 = x + -76 Reorder the terms: -4 + 7x = x + -76 Reorder the terms: -4 + 7x = -76 + x Solving -4 + 7x = -76 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -4 + 7x + -1x = -76 + x + -1x Combine like terms: 7x + -1x = 6x -4 + 6x = -76 + x + -1x Combine like terms: x + -1x = 0 -4 + 6x = -76 + 0 -4 + 6x = -76 Add '4' to each side of the equation. -4 + 4 + 6x = -76 + 4 Combine like terms: -4 + 4 = 0 0 + 6x = -76 + 4 6x = -76 + 4 Combine like terms: -76 + 4 = -72 6x = -72 Divide each side by '6'. x = -12 Simplifying x = -12
| 2x-22=5(1-5x) | | 7x+16(4x-17)=93 | | 42/j=35/55 | | 5q^2+32q+12=23 | | 3/6=k/18 | | x+9=i(5-i) | | 12t+2=4t+20+4t-12 | | 25m-17=18 | | %x75=60 | | %x75=60 | | x/7-2=12 | | 6+x=4x+16 | | 2r^3*r^2= | | -3(x+3)+6x= | | 8x-16+2x+20=180 | | 2p-25=-74+9p | | 7(7-2x)=3 | | (5x+6y)dx+(6x+5y)dy=0 | | 3x+4(2x+5)=31 | | d/3-5=8 | | 18-2y=8 | | 4x-2(17-3x)=20 | | 18-2y=80 | | x-0.6=9.02 | | 475+28b=601 | | 4x+9=59 | | (9x-9)=180 | | x-1/81/2 | | -9x-2.6=-8-2 | | -34t=64 | | 8y-4.2=91.8 | | x^2/3-2x^1/3-15 |